4
$\begingroup$

In my special relativity course the lecture notes say that in four dimensions a rank-2 anti-symmetric tensor has six independent non-zero elements which can always be written as components of 2 3-dimensional vectors, one polar and one axial.

For instance in the angular momentum tensor $L^{ab} = X^aP^b -X^bP^a$ the top row $L^{0i}=ct\vec{p}-(E/c)\vec{x}$ which is obviously polar (as $\vec{x}$ and $\vec{p}$ are polar vectors) while the spatial-spatial section contains the usual 3D angular momentum components which obviously represent the axial angular momentum $\vec{L}$ vector. (And the first column is just -1 times the polar vector due to the anti symmetry of the tensor).

The notes only explain this as ‘these components transforming in identical ways to polar and axial vectors’. I would like to know how to show this, possibly from the co-ordinate transformation rule for a 4D rank 2 contravariant tensor by showing it has equivalent effects of transforming these vector components.

Specifically the notes say ‘it works because those elements do transform as a vector under rotations’. I’m also confused as to why rotations specifically as a transformation are mentioned here.

$\endgroup$
4
$\begingroup$
  1. OP is asking for the branching rules for $$\begin{align}H~:=~&O(3)\cr ~\cong~&\begin{pmatrix} O(3)&\cr &1\end{pmatrix}_{4\times 4}~~\cr ~\subseteq~& O(3,1)~=:~G.\end{align}\tag{1}$$

  2. The 4-vector representation decomposes as $${\bf 4}~\cong~\underbrace{\bf 3}_{\text{vector}}\oplus \underbrace{\bf 1}_{\text{scalar}}.\tag{2}$$

  3. Therefore the tensor product representation becomes $$\begin{align} {\bf 16} ~\cong~& {\bf 4}\otimes{\bf 4}\cr ~\cong~&({\bf 3}\oplus {\bf 1})\otimes({\bf 3}\oplus {\bf 1}) \cr ~\cong~&{\bf 3}\otimes{\bf 3}\oplus \overbrace{\underbrace{{\bf 3}\otimes{\bf 1} \oplus{\bf 1}\otimes{\bf 3}}_{~\cong~{\bf 3}_S ~ \oplus~ {\bf 3}_A}}^{\text{off-diagonal blocks}} \oplus {\bf 1}\otimes{\bf 1}.\tag{3} \end{align}$$ Here ${\bf 3}_S$ and ${\bf 3}_A$ denote the symmetric and antisymmetric combination of the off-diagonal blocks, respectively.

  4. The symmetric part of the tensor product ${\bf 4}\otimes{\bf 4}$ reads $${\bf 10}~\cong~ {\bf 4}\odot{\bf 4} ~\cong~\underbrace{{\bf 3}\odot {\bf 3}}_{~\cong~{\bf 5} ~ \oplus~ {\bf 1}}\oplus {\bf 3}_S \oplus {\bf 1},\tag{4} $$ while the antisymmetric part is

    $$ {\bf 6}~\cong~{\bf 4}\wedge{\bf 4} ~\cong~\underbrace{{\bf 3}\wedge {\bf 3}}_{\text{axial vector}}\oplus \underbrace{{\bf 3}_A}_{\text{vector}} ,\tag{5} $$

    cf. OP's title question. In eq. (5) we used Hodge duality in 3D, cf. e.g. this Phys.SE post.

$\endgroup$
3
$\begingroup$

Qmechanic's answer is beautiful. I'll clarify one non-obvious detail, namely why the $\textbf{3}\wedge \textbf{3}$ transforms as a vector under the identity component of the rotation group. (It doesn't transform as a vector under reflections, which is why we call it an axial vector.)

Let $F_{ab}$ be an antisymmetric tensor in 4d spacetime, and use $0$ for the "time" index and $\{1,2,3\}$ for the "space" indices. When Lorentz transformations are restricted to rotations, the components $F_{jk}$ with $j,k\in\{1,2,3\}$ do not mix with the component $F_{0k}=-F_{k0}$, so we can consider only the components $F_{jk}$. These are the components of the $\textbf{3}\wedge \textbf{3}$ in Qmechanic's answer.


For the rest of this answer, all indices (including $a,b,c$) are restricted to the spatial values $\{1,2,3\}$.

The antisymmetry condition, $F_{jk}=-F_{kj}$, implies that this has only $3$ independent components, which is the correct number of components for a vector, but something doesn't seem quite right: Under rotations, the transformation rule for a vector only uses one rotation matrix, but the transformation rule for $F_{jk}$ uses two rotation matrices — one for each index. How can these possibly be equivalent to each other? Of course they're not equivalent to each other for rotations with determinant $-1$, which is why we call it an axial vector, but they are equivalent to each other for rotations with determinant $+1$, and the purpose of this answer is to explain why that's true.

Let $R_{jk}$ be the components of a rotation matrix whose determinant is $+1$. This condition means $$ \sum_{j,k,m}\epsilon_{jkl}R_{1j}R_{2k}R_{3m} = 1, \tag{1} $$ which can also be written $$ \epsilon_{abc} = \sum_{j,k,m}\epsilon_{jkm}R_{aj}R_{bk}R_{cm}. \tag{2} $$ The fact that $R$ is a rotation matrix also implies $$ \sum_c R_{cm}R_{cn}=\delta_{mn}, \tag{3} $$ which the component version of the matrix equation $R^TR=1$. Contract (2) with $R_{cn}$ and then use (3) to get $$ \sum_c\epsilon_{abc}R_{cn} = \sum_{j,k}\epsilon_{jkn}R_{aj}R_{bk}. \tag{4} $$ Equation (4) is the key. The effect of a rotation on $F_{jk}$ is $$ F_{jk}\to \sum_{a,b}R_{aj}R_{bk}F_{ab}, \tag{5} $$ with one rotation matrix for each index. Since $F_{ab}$ is antisymmetric, we can represent it using only three components like this: $$ v_m\equiv\sum_{j,k}\epsilon_{jkm}F_{jk} \tag{6} $$ The question is, how does $v$ transform under a rotation whose determinant is $+1$? To answer this, use (5) to get $$ v_m\to v_m'=\sum_{j,k}\epsilon_{jkm}\sum_{a,b}R_{aj}R_{bk}F_{ab} \tag{7} $$ and then use (4) to get $$ v_m' =\sum_{a,b,c} \sum_c\epsilon_{abc}R_{cm}F_{ab} =\sum_c R_{cm} v_m. \tag{8} $$ This shows that $v$ transforms like a vector under rotations whose determinant is $+1$.

For rotations whose determinant is $-1$ (reflections), the right-hand side of equation (1) is replaced by $-1$, which introduces a minus sign in equation (4), which ends up putting a minus sign in equation (8). That's why we call $v$ an axial vector instead of just a vector.


More generally, in $N$-dimensional space:

  • Pseudovector and axial vector are synonymous with "completely antisymmetric tensor of rank $N-1$." Intuitively, an ordinary (polar) vector has only one index, and a pseudovector/axial vector is missing only one index. As a result, they both transform the same way under rotations, but only under rotations. They transform differently in other respects, including relfections and dilations.

  • Under an arbitrary coordinate transform, a (polar) vector transforms as $v_{j}\to \Lambda^a_j v_{a}$.

  • Under an arbitrary coordinate transform, a rank-2 tensor transforms as $F_{jk}\to \Lambda^a_j\Lambda^b_k F_{ab}$. (The components of $\Lambda$ are the partial derivatives of one coordinate system's coordinates with respect to the other's. Sums over repeated indices are implied.)

  • If $N\neq 3$, then angular momentum is an antisymmetric rank-2 tensor (also called a bivector), not an axial vector. A bivector has 2 indices, but an axial vector has $N-1$ indices.

  • To illustrate the different transformation laws for (polar) vectors and bivectors, consider a dilation (also called dilatation) that multiplies the spatial coordinates by a constant factor $\kappa$. Then each factor of $\Lambda$ contributes one factor of $\kappa$, so $F_{jk}\to\kappa^2 F_{jk}$, but a vector goes like $v_j\to \kappa v_j$.

Axial vectors and bivectors are the same in 3d space, but they are not really vectors at all, even though they both happen to have 3 components in 3d space. If we only consider rotations (with determinant $+1$), then they might as well be vectors, but even that's only true in 3d space, not in other-dimensional spaces.

$\endgroup$
1
  • 1
    $\begingroup$ Comments are not for extended discussion; this conversation has been moved to chat. $\endgroup$
    – tpg2114
    Jan 2 at 17:40
0
$\begingroup$

Reference : My answer here Vector product in a 4-dimensional Minkowski spacetime.

$=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=$

In my above referenced answer from two 4-vectors $\mathbf{X}\boldsymbol{=}\left(\mathbf{x},x_4\right)$ and $\mathbf{P}\boldsymbol{=}\left(\mathbf{p},p_4\right)$, see also equations (15a) and (15b) therein, we had defined as their outer product the antisymmetric $4\times 4$ matrix \begin{equation} \left[\,\mathbf{H}\,\right] \boldsymbol{=}\left[\,\mathbf{X}\boldsymbol{\times}\mathbf{P}\,\right]\boldsymbol{\equiv} \begin{bmatrix} \begin{array}{ccc|c} \hphantom{\boldsymbol{=}}0 & \boldsymbol{-}\mathrm h_3 & \boldsymbol{+}\mathrm h_2 & \boldsymbol{+}\mathrm g_1\vphantom{\dfrac{a}{b}}\\ \boldsymbol{+}\mathrm h_3 & \hphantom{\boldsymbol{=}}0 & \boldsymbol{-}\mathrm h_1 & \boldsymbol{+}\mathrm g_2\vphantom{\dfrac{a}{b}}\\ \boldsymbol{-}\mathrm h_2 & \boldsymbol{+}\mathrm h_1 & \hphantom{\boldsymbol{=}}0 & \boldsymbol{+}\mathrm g_3\vphantom{\dfrac{a}{b}}\\ \hline \boldsymbol{-}\mathrm g_1 & \boldsymbol{-}\mathrm g_2 & \boldsymbol{-}\mathrm g_3 & \hphantom{\boldsymbol{=}}0\vphantom{\dfrac{a}{b}} \end{array} \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ & \mathbf{h}\boldsymbol{\times} & & \mathbf{g} \vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \boldsymbol{-}\mathbf{g}^{\mathsf{T}} & & 0\vphantom{\dfrac{a}{b}} \end{array} \end{bmatrix} \tag{A-01}\label{A-01} \end{equation} where \begin{equation} \mathbf{h}\boldsymbol{=}\mathbf{x}\boldsymbol{\times}\mathbf{p}\,,\quad \mathbf{g}\boldsymbol{=}x_4\mathbf{p}\boldsymbol{-}p_4\mathbf{x} \tag{A-02}\label{A-02} \end{equation} For the details of this definition see equations (16)-(21) therein.

Moreover, based on this, from the space-time position and relativistic linear momentum of a particle respectively \begin{equation} \mathbf{X} \boldsymbol{=}\left(\mathbf{x}, ct\right) \qquad \mathbf{P} \boldsymbol{=}\left(\gamma m_{0}\mathbf{u}, \gamma m_{0} c\right) \tag{A-03}\label{A-03} \end{equation} we had defined as relativistic angular momentum the antisymmetric $4\times 4$ matrix \begin{equation} \left[\,\mathbf{H}\,\right] \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ & \left[\,\mathbf{x}\boldsymbol{\times}\mathbf{p}\,\right] & & \left(ct\mathbf{p}\boldsymbol{-}\gamma m_{0}c\mathbf{x}\vphantom{\tfrac{a}{b}}\right) \vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \boldsymbol{-}\left(ct\,\mathbf{p}\boldsymbol{-}\gamma m_{0}c\,\mathbf{x}\vphantom{\tfrac{a}{b}}\right)^{\mathsf{T}} & & 0\vphantom{\dfrac{\tfrac{a}{b}}{b}} \end{array} \end{bmatrix} \tag{A-04}\label{A-04} \end{equation} the real 6-vector $\mathbf{H}$ being (as in the question) \begin{equation} \mathbf{H} \boldsymbol{=} \begin{bmatrix} \mathbf{h}\vphantom{\dfrac{\tfrac{a}{b}}{b}}\\ \mathbf{g}\vphantom{\dfrac{a}{\tfrac{a}{b}}} \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \mathbf{x}\boldsymbol{\times}\mathbf{p}\vphantom{\dfrac{\tfrac{a}{b}}{b}}\\ ct\mathbf{p}\boldsymbol{-}\gamma m_{0}c\mathbf{x}\vphantom{\dfrac{a}{\tfrac{a}{b}}} \end{bmatrix} \tag{A-05}\label{A-05} \end{equation} It's interesting to see how the antisymmetric $4\times 4$ matrix $\left[\,\mathbf{H}\,\right]$ of equation \eqref{A-01} is transformed under a Lorentz boost \begin{equation} \mathrm L \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ &\mathrm I\boldsymbol{+}\dfrac{\gamma^2}{c^2\left(\gamma\boldsymbol{+}1\right)}\boldsymbol{\upsilon}\boldsymbol{\upsilon}^{\mathsf{T}} & & \boldsymbol{-}\gamma\dfrac{\boldsymbol{\upsilon}}{c}\vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \boldsymbol{-}\gamma\dfrac{\boldsymbol{\upsilon}^{\mathsf{T}}}{c} & & \gamma\vphantom{\dfrac{\dfrac{a}{b}}{b}} \end{array} \end{bmatrix} \tag{A-06}\label{A-06} \end{equation} We have \begin{equation} \left[\,\mathbf{H}'\,\right] \boldsymbol{=}\left[\,\mathbf{X}'\boldsymbol{\times}\mathbf{P}'\,\right]\boldsymbol{=}\left[\,\left(\mathrm L\mathbf{X}\right)\boldsymbol{\times}\left(\mathrm L\mathbf{P}\right)\,\right]\boldsymbol{=}\mathrm L\left[\,\mathbf{X}\boldsymbol{\times}\mathbf{P}\,\right]\mathrm L \boldsymbol{=}\mathrm L\left[\,\mathbf{H}\,\right]\mathrm L \tag{A-07}\label{A-07} \end{equation} hence \begin{equation} \left[\,\mathbf{H}'\,\right] \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ & \mathbf{h}'\boldsymbol{\times} & & \mathbf{g}' \vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \boldsymbol{-}\mathbf{g}'^{\mathsf{T}} & & 0\vphantom{\dfrac{a}{b}} \end{array} \end{bmatrix} \tag{A-08}\label{A-08} \end{equation} where \begin{align} \mathbf{h}' & \boldsymbol{=} \gamma\mathbf{h}\boldsymbol{-}\dfrac{\gamma^2}{c^2\left(\gamma\boldsymbol{+}1\right)}\left(\mathbf{h}\boldsymbol{\cdot}\boldsymbol{\upsilon}\right)\boldsymbol{\upsilon}\vphantom{A^{1/2}}\boldsymbol{-}\dfrac{\gamma}{c}\left(\boldsymbol{\upsilon}\boldsymbol{\times}\mathbf{g}\vphantom{A^2}\right) \tag{A-09a}\label{A-09a}\\ \mathbf{g}' & \boldsymbol{=}\gamma\mathbf{g}\boldsymbol{-}\dfrac{\gamma^2}{c^2\left(\gamma\boldsymbol{+}1\right)}\left(\mathbf{g}\boldsymbol{\cdot}\boldsymbol{\upsilon}\vphantom{A^2}\right)\boldsymbol{\upsilon}\boldsymbol{+}\dfrac{\gamma}{c}\left(\boldsymbol{\upsilon}\boldsymbol{\times}\mathbf{h}\vphantom{A^2}\right) \tag{A-09b}\label{A-09b} \end{align} If, by a similar way, we apply the Lorentz boost \eqref{A-06} to the antisymmetric matrix of the electromagnetic field \begin{equation} \mathcal{E\!\!\!\!E} \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ & \left[\,c\,\mathbf{B}\,\right] & & \boldsymbol{+}\mathbf{E} \vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \boldsymbol{-}\mathbf{E}^{\boldsymbol{\top}} & & 0\vphantom{\dfrac{a}{b}} \end{array} \end{bmatrix} \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} 0 & \boldsymbol{-}c\,B_3 & \boldsymbol{+}c\,B_2 & \boldsymbol{+}E_1\vphantom{\dfrac{a}{b}}\\ \boldsymbol{+}c\,B_3 & 0 & \boldsymbol{-}c\,B_1 & \boldsymbol{+}E_2 \vphantom{\dfrac{a}{b}}\\ \boldsymbol{-}c\,B_2 & \boldsymbol{+}c\,B_1 & 0 & \boldsymbol{+}E_3\vphantom{\dfrac{a}{b}}\\ \hline \boldsymbol{-}E_1 & \boldsymbol{-}E_2 & \boldsymbol{-}E_3 & 0\vphantom{\dfrac{a}{b}} \end{array} \end{bmatrix} \tag{A-10}\label{A-10} \end{equation} see equations (28)-(31) in my referenced answer, then we have \begin{align} \mathbf{B}' & \boldsymbol{=} \gamma \mathbf{B}\boldsymbol{-}\dfrac{\gamma^2}{c^2\left(\gamma\boldsymbol{+}1\right)}\left(\mathbf{B}\boldsymbol{\cdot}\boldsymbol{\upsilon}\right)\boldsymbol{\upsilon}\vphantom{A^{1/2}}\boldsymbol{-}\dfrac{\gamma}{c^2}\left(\boldsymbol{\upsilon}\boldsymbol{\times}\mathbf{E}\vphantom{A^{1/2}}\right) \tag{A-11a}\label{A-11a}\\ \mathbf{E}' & \boldsymbol{=} \gamma\mathbf{E}\boldsymbol{-}\dfrac{\gamma^2}{c^2\left(\gamma\boldsymbol{+}1\right)}\left(\mathbf{E}\boldsymbol{\cdot}\boldsymbol{\upsilon}\vphantom{A^2}\right)\boldsymbol{\upsilon}\boldsymbol{+}\gamma\left(\boldsymbol{\upsilon}\boldsymbol{\times}\mathbf{B}\vphantom{A^2}\right) \tag{A-11b}\label{A-11b} \end{align} as we meet in many textbooks and answers in PSE.

Under the $4\times 4$ transformation \begin{equation} \mathrm R \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ &\hphantom{==}\mathcal R \hphantom{==}& & \hphantom{=}\mathbf{O}\hphantom{=}\vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \mathbf{O}^{\boldsymbol{\top}} & & 1\vphantom{\dfrac{\dfrac{a}{b}}{b}} \end{array} \end{bmatrix} \tag{A-12}\label{A-12} \end{equation}
where $\mathcal R$ is an orthonormal $3\times 3$ matrix \begin{equation} \mathcal R \mathcal R^{\mathsf{T}}\boldsymbol{=}\mathrm I_{3\times 3}\boldsymbol{=}\mathcal R^{\mathsf{T}}\mathcal R \,,\qquad \boldsymbol{\vert} \det(\mathcal R)\boldsymbol{\vert}\boldsymbol{=}1 \tag{A-13}\label{A-13} \end{equation}
the antisymmetric $4\times 4$ matrix $\left[\,\mathbf{H}\,\right]$ of equation \eqref{A-01} is transformed as follows \begin{equation} \left[\,\mathbf{H}'\,\right] \boldsymbol{=}\left[\,\mathbf{X}'\boldsymbol{\times}\mathbf{P}'\,\right]\boldsymbol{=}\left[\,\left(\mathrm R\mathbf{X}\right)\boldsymbol{\times}\left(\mathrm R\mathbf{P}\right)\,\right]\boldsymbol{=}\mathrm R\left[\,\mathbf{X}\boldsymbol{\times}\mathbf{P}\,\right]\mathrm R^{\mathsf{T}} \tag{A-14}\label{A-14} \end{equation} hence \begin{equation} \left[\,\mathbf{H}'\,\right] \boldsymbol{=} \begin{bmatrix} \begin{array}{ccc|c} & & & \vphantom{\dfrac{a}{b}}\\ & \mathbf{h}'\boldsymbol{\times} & & \mathbf{g}' \vphantom{\dfrac{a}{b}}\\ & & & \vphantom{\dfrac{a}{b}}\\ \hline & \boldsymbol{-}\mathbf{g}'^{\mathsf{T}} & & 0\vphantom{\dfrac{a}{b}} \end{array} \end{bmatrix} \tag{A-15}\label{A-15} \end{equation} where \begin{align} \!\!\!\!\!\!\!\!\!\!\!\!\!\!\mathbf{h}'\boldsymbol{\times} & \boldsymbol{=} \mathcal R \left(\mathbf{h}\boldsymbol{\times}\right)\mathcal R^{\mathsf{T}}\boldsymbol{=}\mathcal R \left[\left(\mathbf{x}\boldsymbol{\times}\mathbf{p}\right)\boldsymbol{\times}\vphantom{\tfrac{a}{b}}\right]\mathcal R^{\mathsf{T}} \nonumber\\ & \boldsymbol{=}\left[\mathcal R\mathbf{x}\boldsymbol{\times}\mathcal R\mathbf{p}\vphantom{\tfrac{a}{b}}\right]\boldsymbol{\times}\stackrel{\eqref{A-18}}{\boldsymbol{=\!=\!=}}\det(\mathcal R)\cdot\left[\mathcal R \left(\mathbf{x}\boldsymbol{\times}\mathbf{p}\right)\vphantom{\tfrac{a}{b}}\right]\boldsymbol{\times}\boldsymbol{=}\det(\mathcal R)\cdot\mathcal R\mathbf{h}\boldsymbol{\times}\boldsymbol{\Longrightarrow} \nonumber\\ \mathbf{h}'& \boldsymbol{=}\det(\mathcal R)\cdot\mathcal R\mathbf{h} \tag{A-16a}\label{A-16a}\\ \mathbf{g}' & \boldsymbol{=}\mathcal R \mathbf{g} \tag{A-16b}\label{A-16b} \end{align}

$=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=\!=$

If $\:\mathbf{a},\:\mathbf{b} $ are complex $\:3$-vectors in $\:\mathbb{C}^{3}\:$ and $\:\mathcal M\:$ an invertible linear transformation in this space then \begin{equation} \mathcal M\mathbf{a} \boldsymbol{\times} \mathcal M\mathbf{b} \boldsymbol{=} \left[\;\det\left(\mathcal M\right)\cdot\left(\mathcal M^{-1}\right)^{\mathsf{T}}\; \right]\left(\mathbf{a} \boldsymbol{\times}\mathbf{b}\right) \tag{A-17}\label{A-17} \end{equation} If moreover $\:\mathcal M\:$ is a real orthonormal matrix then $\left(\mathcal M^{-1}\right)^{\mathsf{T}}\boldsymbol{=}\mathcal M$ and $\det\left(\mathcal M\right)\boldsymbol{=}\boldsymbol{\pm}1$ hence \begin{equation} \mathcal M\mathbf{a} \boldsymbol{\times} \mathcal M\mathbf{b} \boldsymbol{=} \det\left(\mathcal M\right)\cdot\mathcal M\left(\mathbf{a} \boldsymbol{\times}\mathbf{b}\right)\boldsymbol{=}\boldsymbol{\pm}\,\mathcal M\left(\mathbf{a} \boldsymbol{\times}\mathbf{b}\right) \tag{A-18}\label{A-18} \end{equation} For a proof of identity \eqref{A-17} see $\textbf{Section B}$ in my answer as user82794 (former diracpaul) here

How to get result $\boldsymbol{3}\boldsymbol{\otimes}\boldsymbol{3} =\boldsymbol{6}\boldsymbol{\oplus}\bar{\boldsymbol{3}}$ for SU(3) irreducible representations?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.